2003
DOI: 10.1523/jneurosci.23-19-07407.2003
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neural Synchrony in Schizophrenia

Abstract: Schizophrenia has been conceptualized as a failure of cognitive integration, and abnormalities in neural circuitry (particularly inhibitory interneurons) have been proposed as a basis for this disorder. We used measures of phase locking and phase coherence in the scalp-recorded electroencephalogram to examine the synchronization of neural circuits in schizophrenia. Compared with matched control subjects, schizophrenia patients demonstrated: (1) absence of the posterior component of the early visual gamma band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
433
3
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(482 citation statements)
references
References 26 publications
40
433
3
6
Order By: Relevance
“…These findings are significant in several ways. First, our findings confirm reported P1 deficits in patients compared to controls (Basinska, 1998;Doniger et al, 2002;Foxe et al, 2001;Matsuoka et al, 1996;Romani et al, 1986;Spencer et al, 2003). Furthermore, the fact that the P1 component was particularly prominent in the low contrast (M) and high contrast (mixed M/P) conditions but not in the chromatic contrast (P) condition is further indication of the M genesis of this component (Di Russo et al, 2001;Ellemberg et al, 2001;Previc, 1988).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are significant in several ways. First, our findings confirm reported P1 deficits in patients compared to controls (Basinska, 1998;Doniger et al, 2002;Foxe et al, 2001;Matsuoka et al, 1996;Romani et al, 1986;Spencer et al, 2003). Furthermore, the fact that the P1 component was particularly prominent in the low contrast (M) and high contrast (mixed M/P) conditions but not in the chromatic contrast (P) condition is further indication of the M genesis of this component (Di Russo et al, 2001;Ellemberg et al, 2001;Previc, 1988).…”
Section: Discussionsupporting
confidence: 88%
“…Initial, as well as current, studies of the tVEP (Shagass et al, 1977;Straumanis et al, 1982;van der Stelt et al, 2004) have found no impairment in the early components of the waveform, reporting a deficit only at 200 ms (Shagass, 1980) or later (van der Stelt et al, 2004). In other studies, however, significant P1 deficits have been observed (Basinska, 1998;Doniger et al, 2002;Foxe et al, 2001;Matsuoka et al, 1996;Romani et al, 1986;Spencer et al, 2003). Stimulus types, recording characteristics (e.g., filter frequencies) and patient types have varied considerably across studies, leaving the basis for the divergence in results unresolved.…”
Section: Introductionmentioning
confidence: 96%
“…Gamma oscillatory deficits have been observed in schizophrenia under a wide range of experimental conditions, including in the resting state (Yeragani et al, 2006), elicited by TMS (Ferrarelli et al, 2008), with relatively simple perceptual task demands (Spencer et al, 2003;Spencer et al, 2004;Spencer et al, 2008a), in relation to motor responses (Ford et al, 2008), and with more complex cognitive demands (Cho et al, 2006), including this study. Taken together, these findings suggest that cortical oscillatory dysfunction may be a general feature of this illness.…”
Section: Discussionmentioning
confidence: 81%
“…Gamma activity has also been studied in schizophrenia using tasks with more complex processing demands. These studies have found schizophrenia patients to exhibit relatively lower frequency (Spencer et al, 2004) and decreased synchrony (Spencer et al, 2003) of an oscillation that is phase-locked to motor response in a Gestalt perception task, although others have found preserved gamma power in a different Gestalt perception task (Uhlhaas et al, 2006). Task demands with a stronger PFC-dependence have also revealed gamma deficits in schizophrenia patients, including impaired frontal gamma power (measured by magnetoencephalography) during mental arithmetic performance (Kissler et al, 2000) and an inability to mount increased delay-period gamma power in response to increasing working memory load during the N-Back (Basar-Eroglu et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Gamma oscillations are synchronized over long distances in the brain and are hypothesized to 'bind' together sensory perceptions and to play a role in cognition (reviewed in Wilson and Nicoll, 2002). Abnormalities in gamma band synchronization have been reported in schizophrenia (Spencer et al, 2003). Activation of these presynaptic CB1Rs reduces GABA release by interneurons (Sullivan, 1999;Katona et al, 1999a), which in turn would disrupt the synchronization of pyramidal cell activity (Wilson and Nicoll, 2002;Hoffman and Lupica, 2000), thereby interfering with associative functions, disrupting normal gating mechanisms, and eventually inducing psychotic symptoms.…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%